Short-Term Prognostic Predictive Evaluation in Female Patients With Ischemic Stroke: A Retrospective Cross-Sectional Study - Eren, Fettah; Ozguncu, Cihat; Ozturk, Serefnur (Frontiers in Neurology, 2022)
Introduction and Aim Stroke is a disease with high mortality and morbidity. Although studies are generally performed on all patients with stroke, it is known that gender has an effect on etiology and prognosis. This study aimed to determine the importance of clinical stroke scales and laboratory markers in determining the short-term prognosis of female patients with ischemic stroke of anterior circulation. Materials and Methods The study was planned as a retrospective and cross-sectional study. SEDAN score, the National Institutes of Health stroke scale (NIHSS), the Modified Rankin Scale (mRS), the Glasgow Coma Scale (GCS), and THRIVE score applied to the patients at the time of admission were recorded. Admission blood glucose, hemoglobin, leukocyte, urea, albumin, and blood lipid levels were evaluated. The relationship of all these parameters with in-hospital prognosis, mortality, and disability at discharge was examined. The relationship between groups and data was analyzed using the SPSS package program after the normality analysis. Results In this study, there were 733 female patients with stroke with a mean age of 69.53 ± 14.51 years and 858 male patients with stroke with a mean age of 64.27 ± 13.29 years. Hospitalization time, length of stay in the intensive care unit, ventilation need rate, mortality, and dependency rate were higher in female patients (p = 0.001). The NIHSS, SEDAN, and THRIVE scores were higher in female patients who had in-hospital mortality, had a poor prognosis, and who were discharged as dependent (p = 0.001). GCS was lower in this patient group (p = 0.001). Blood glucose, creatinine, leukocytes, urea, and CRP levels were higher; the albumin and hemoglobin levels was lower in female patients who had fatal outcomes (p = 0.009, 0.001, 0.001, 0.001, 0.001, and 0.020; respectively). In female patients who were dependent at discharge, blood urea, glucose, and CRP levels were higher and the albumin levels were lower than those in female patients who achieved functional independence (p = 0.001, 0.016, 0.002, and 0.001, respectively). Conclusion Our study showed that the short-term prognosis is worse in female patients who had an ischemic stroke of anterior circulation. It also revealed some clinical and laboratory parameters that could predict this situation. More intensive monitoring may be needed to improve prognosis in female patients.